Security System Using GSM - RAMESH BABU N (2003)
INTERNAL GUIDE : Patil B Shantakumar. EXTERNAL GUIDE: Haneef Nawaz USN No : 1MJ02SCS09 CARRIED OUT AT : Chip Integration Technologies Ltd Bangalore-560 040 ACC NO : PC15
Keywords: M.Tech Computer Science